Educational games and learning in Chemistry: a view of PIBID supervising teachers (Research, Society and Development, 2020)
In view of several works in the literature that discuss the subject, a proposal for the chemistry teaching becomes more active and less decorative is through educational games, which can be used at different times, as in the exhibition of content, representation relevant knowledge on different topics, evaluation or synthesis of important concepts of subjects already developed. In this context, the aim was to investigate what educational games have provided in the teaching-learning process. This work is qualitative and is inserted as a case study. For this, interview was made with high school teachers who participate in the Programa Institucional de Bolsas de Iniciação à Docência (PIBID), to understand their concepts about didactic games. The results obtained with the interview were formed and we understand that the use of educational games, in the interviewees' view, is a promising methodological tool to help students to learn the subject inserted in the classroom. In view of what has been observed, the viability of games can be fulfilled as a methodology that contributes positively to the teaching-learning process of students in content involving Chemistry.